Effect of In ovo Injection of Acetic Acid on Hatching Characteristics, Bio Intestine Measures And Weight Gain of Broiler Chickens - Al-Azzawi, Ali Mohammed Abdul Rahim; Jassim, Mahdi Saleh; Azzawi, Amer Khazaal (Journal of agricultural, environmental and veterinary sciences, 2018)
This study in order to in the Poultry Farm of Animal Production Department- College of Agriculture- University of Diyala to investigate the effect of In ovo injecting of different levels of Acetic Acid solution on hatching characteristics, bio intestine measures and weight gain of broiler chickens. Hatching eggs are used from breeders of the broiler (Ross308), distributed into six treatments, T1(hatching eggs without injection), T2 (hatching eggs are injected 0.2 ml/ egg distilled water only), and T3, T4, T5, T6 hatching eggs are injected 1, 2, 3, 4 μl /egg respectively, after injection, the eggs were returned to the hatcher. on hatching 255 broiler chicks were used, their took from the chicks of the best two treatments in the results that’s means the fifth and sixth treatments (T5, T6) as well as the treatment of control (T1) form randomly and an equal number of 75 chicks of each treatment, they were raised in standard conditions up to the age of 35 days. The results of hatching showed significant Increased (P ≥ 0.05) in the hatchability of healthy chicks, significant decreased (P ≤ 0.01) in the hatchability of distorted chicks in all acid injection treatments, and significant decreased in the hatchability of embryo mortality in both of acid injection treatments T5, T6, and significant Increased in the total hatchability in all acid injection treatments, and significant decreased in the weight of remaining yolk, improved significantly in both relative body weight and weight gain, and bio intestine measures in the chicks, while the eggs of acetic acid injection treatments weren’t significantly effect on daily Feed intake compared with birds of control treatment.